Synthesis, crystal structure and bioactivities of α‐asaronol. Issue 5 (5th April 2022) - Zhang, Qun-Zheng; Zhong, Zhen-Hua; Hao, Ding; Feng, Ming-Nan; Wang, Si-Chang; Han, Qi-Long; Bai, Yajun; Xu, Danni; Liao, Sha; Xiao, Chaoni; Zhang, Xun-Li; Zheng, Xiaohui
Abstract : α‐Asaronol [or ( E )‐3′‐hydroxyasarone] was synthesized, grown as single crystals, characterized and further evaluated for neuroprotective activities towards the development of a potential antiepileptic drug. Abstract : α‐Asaronol [or ( E )‐3′‐hydroxyasarone; systematic name: ( E )‐3‐(2, 4, 5‐trimethoxyphenyl)prop‐2‐en‐1‐ol; C12 H16 O4 ] was synthesized towards the development of a potential antiepileptic drug. Following purification by recrystallization, single crystals of α‐asaronol were obtained by a liquid interface diffusion method at room temperature. The product was characterized by 1 H and 13 C NMR, and FT–IR spectroscopic analysis. X‐ray crystallography revealed the title crystal to belong to the orthorhombic space group P 21 21 21 . Preliminary bioassays with mouse neuroblastoma N2a cells demonstrated the neuroprotective activities of the synthesized α‐asaronol.